Concentrated photovoltaic thermal systems: A component-by-component view on the developments in the design, heat transfer medium and applications. (15th April 2019) - George, Mathew; Pandey, A.K.; Abd Rahim, Nasrudin; Tyagi, V.V.; Shahabuddin, Syed; Saidur, R.
Highlights: Comprehensive review on heat transfer, device design and limitation of Concentrated Photovoltaic Thermal system. Component wise thorough discussion on design and limitations of Concentrated Photovoltaic Thermal system. Discussion on economic feasibility and recent novel applications of Concentrated Photovoltaic Thermal system. Presents recent trends and move in Concentrated Photovoltaic Thermal system research. Abstract: The need of the hour in present world scenario is to reduce the emission of greenhouse gases and environmental pollution whilst satisfying the world energy demands. The most promising and readily available source of energy over the whole world is solar energy. One of the ways of taping this energy into useful energy is using Concentrated Photovoltaic Thermal systems. The paper presents the advanced comprehensive review on the design components of Concentrated Photovoltaic Thermal, heat transfer medium, recent application area such as Tissue Dyeing, domestic hot water, Organic Rankine Cycle, and the economic aspect of the Concentrated Photovoltaic Thermal system. Furthermore, the review paper simplifies the classification into two systems namely thermally coupled and thermally decoupled systems. Concentrated Photovoltaic Thermal shows potential to deliver better gains compared to Concentrated Photovoltaic, Photovoltaic and Photovoltaic Thermal. But matching the different components like the heat transfer component and the medium for specific use is an area that requires research. Therefore, this review concentrates more on the advantages and limitations of using different heat transfer components and heat transfer medium. The benefits of this paper would be the understanding of the components of the heat transport system like fins, microchannel, storage tank and underground heat exchangers and the fluid used in the Concentrated Photovoltaic Thermal integrated system like water, air, nanofluids, Phase Change Materials. It is found that the heat transfer device performance is limited due to its large area, thermal losses, mirror effect on the thermal and electrical efficiencies, and the temperature difference between the sink and device. Likewise, the performance of the heat transfer fluid is dependent on the mass flow rate, thermal mass, viscosity, density, time and the required temperature. Finally, for economic feasibility of the Concentrated Photovoltaic Thermal system requires the need for a grid connected system with properly sized system with feed-in-tariff and carbon incentives. Furthermore, the recommendation for heat transfer device, medium and economic aspect is also presented. However, more experimental research is required to further understand the compatibility of each components with Concentrating Photovoltaic Thermal System as presented in way forward.